Fine-tuning deep belief networks using cuckoo search - Rodrigues, D.; Yang, X. S.; Papa, J. P. [UNESP] (Elsevier, 2016)
In the last few years, metaheuristic-driven optimization has been employed to address deep belief network (DBN) model selection, since it provides simple and elegant solutions in a wide range of applications. In this work, we introduce the well-known cuckoo search to fine-tune DBN parameters and validate its effectiveness by comparing it with harmony search, improved harmony search, and particle swarm optimization. The experimental results have been carried out in two public datasets using DBNs with a different number of layers concerning the task of binary image reconstruction.
Keywords: Cuckoo search; Deep belief networks; Harmony search; Metaheuristic; Model selection; Particle swarm optimization